A-Vista: New challenges for tailor-made translation types on the example of the recorded sight translation - Biela-Wolonciej, Aleksandra (Kalbotyra, 2007)
With the growing market for language services, the changing needs of clients, and the technological advance, arise new tailor-made types of translation that fall in-between the traditional categories (such as oral/written, simultaneous/consecutive, transient/permanent, etc.), attempting to combine their advantages and best suit the given purpose. Initially inspired by a practitioner’s point of view, enhanced by a theoretical analysis, the paper presents the characteristics of a type of sight translation that is recorded for the client, which seems to be a very convenient form and an optimal solution for certain purposes.